THE EFFECT OF EXPERIENTIAL MARKETING AND E-SERVICE QUALITY ON CUSTOMER SATISFACTION WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Adam Aulla Priatmojo; Henny Welsa; Agus Dwi Cahya (STKIP Singkawang, 2023)
This study aims to test and analyze the influence of Experiential Marketing and E-Service Quality on customer satisfaction with brand image as an intervening variable. The population in the study was consumers of Dazzle Gejayan. The technique used in sampling in this study was purposive sampling, and a total sample of 100 Dazzle Gejayan consumers was obtained as respondents. Data collection was carried out using the questionnaire method, then the data obtained were processed using Statistical Product and Service Solutions (SPSS) versi 22. The results of this study show that Experiential Marketing has a positive and significant effect on Brand Image, E-Service Quality has a positive and significant effect on Brand Image, Brand Image has a positive and significant effect on Customer Satisfaction, Experiential Marketing has a positive and significant effect on Customer Satisfaction, E-Service Quality has a positive and significant effect on Customer Satisfaction Customer Satisfaction, directly Experiential Marketing does not have a significant effect on Customer Satisfaction through Brand Image, and directly E-Service Quality does not affect Customer Satisfaction through Brand Image.